The effects of personal values and environmentalist consumer behavior on environmental-friendly product loyalty - AYSUNA TÜRKYILMAZ, CEYDA (My University, 2021)
The problem of depletion of world resources is an important issue today and climate change has brought the importance of this issue to the agenda. The high sensitivity of consumers, with the increasing consciousness, environmental events has triggered the careful use of resources in the context of the sustainability phenomenon, and gave rise to many discussion and researched in many scientific fields. Sustainability requires transformation in both “production” and “consumption” habits. The increase in environmental awareness has a very effective power in the evolution of our consumption preferences, which we determine in line with our individual and collective goals. Environmental awareness has accelerated the consumers' tendency to demand clean and environmentally friendly products. Businesses which are described as environmentally friendly, on the other hand, have started to produce environmentally friendly products. There are many factors that affect consumers' tendency towards environmentally friendly products, but it should be underlined that the personal values of consumers come to the fore on the basis of environmentalist consumer behavior. In this study, the effect of personal values consisting of power, universalism, hedonism, achievement and benevolence and environmentalist consumer behavior on environmentalfriendly product loyalty were investigated. The population of the research consists of consumers aged 18 and over living in Istanbul. In the analysis of the research model of the study, which was carried out by applying a questionnaire to 299 consumers, which were reached by convenience sampling method, the effects of the variables on each other were tested, and various suggestions on environmental consumer behavior were developed based on the findings.

Dünya kaynaklarının tükenmesi sorunu günümüzde önemli bir konudur ve iklim değişikliği de bu konunun önemini daha da gündeme taşımıştır. Bilinç düzeyi artan tüketicilerin çevre olaylarına yönelik gösterdikleri yüksek duyarlılık, sürüdürülebilirlik olgusu bağlamında kaynakların dikkatli kullanımını tetikleyerek birçok bilim alanında tartışılmasına ve araştırılmasına neden olmuştur. Sürdürülebilirlik, hem “üretim” hem de “tüketim” alışkanlıklarında dönüşüm gerektirmektedir. Çevre bilinci farkındalığındaki artış, bireysel ve kolektif hedeflerimiz doğrultusunda belirlediğimiz tüketim tercihlerimizin evrilmesinde oldukça etkili bir güce sahiptir. Çevreye duyarlılık bilinci tüketicilerin temiz ve çevreci ürünleri talep etme eğilimini hızlandırmıştır. Günümüz tüketicileri giderek daha sürdürülebilir çevre dostu standartlara sahip ürünleri talep etmeye yönelmişlerdir. İşletmeler ise bu talebe yönelik çevre dostu olarak tarif edilen çevreci ürünler üretmeye başlamışlardır. Tüketicilerin çevre dostu ürünlere yönelmelerini etkileyen birçok faktör sayılabillir ancak çevreci tüketici davranışının temelinde tüketicilerin kişisel değerlerinin öne çıktığının altı çizilmelidir. Bu çalışmada; güç, evrenselcilik, hazcılık, başarı ve iyilikseverlik boyutlarından oluşan kişisel değerlerin ve çevreci tüketici davranışının, çevre dostu ürün sadakati üzerindeki etkisi araştırılmıştır. Araştırmanın anakütlesini İstanbul ilinde yaşayan 18 yaş ve üzeri tüketiciler oluşturmaktadır. Kolayda örneklem yöntemiyle ulaşılan 299 tüketici üzerine anket uygulanarak yürütülen çalışmanın araştırma modelinin analizinde değişkenlerin birbirlerine olan etkileri test edilmiş olup elde edilen bulgulardan hareketle çevreci tüketici davranışı üzerine çeşitli öneriler geliştirilmiştir
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Sürdürülebilir Çevre; Çevreci Tüketici Davranışı; Kişisel Değerler; Çevre Dostu Ürün; Sustainable Environment; Environmentalist Consumer Behavior; Personal Values; Environmental-Friendly Product